Bacteroides vulgatus SNUG 40005 Restores Akkermansia Depletion by Metabolite Modulation - You, Hyun Ju; Si, Jiyeon; Kim, Jinwook; Yoon, Sunghyun; 차광현; Yoon Hyo Shin; 이길재; 유준선; 최준선; 정민경; 김도준; 이유진; et al. (W. B. Saunders Co., Ltd., 2023)
BACKGROUND & AIMS: Weight loss and exercise intervention have been reported to increase the interaction between Bac-teroides spp and Akkermansia muciniphila (Am), although the underlying mechanisms and consequences of the interaction remain unknown. METHODS: Using a healthy Korean twin cohort (n= 582), we analyzed taxonomic associations with host body mass index. B vulgatus strains were isolated from mice and human subjects to investigate the strain-specific effect of Bvul-gatus SNUG 40005 (Bvul) on obesity. The mechanisms underlying Am enrichment by Bvul administration were investigated multiple experiments: (1) in vitro cross-feeding experiments, (2) construction of Bvul mutants with the N-acetylglucosaminidase gene knocked out, and (3) in vivo validation cohorts with different metabolites. Finally, metabolite profiling in mouse and human fecal samples was performed. RESULTS: An interaction between Bvul and Am was observed in lean subjects but was disrupted obese subjects. The administration of Bvul to mice fed a high-fat diet decreased body weight, insulin resistance, and gut perme-ability. In particular, Bvul restored the abundance of Am, which decreased significantly after a long-term high-fat diet. A cross-feeding analysis of Am with cecal contents or Bvul revealed that Am enrichment was attributed to metabolites produced during mucus degradation by Bvul. The metabolome profile of mouse fecal samples identified N-acetylglucosamine as contributing to Am enrichment, which was confirmed by in vitro and in vivo experiments. Metabolite network analysis of the twin cohort found that lysine serves as a bridge between N-acetylglucosamine, Bvul, and Am. CONCLUSIONS: Strain-specific microbe-microbe interactions modulate the mucosal environment via metabolites produced during mucin degradation in the gut.